Study of Earning Management and Audit Quality in Indonesia - Rika Puspita Sari; Rida Perwita Sari (Journal of Economics, Business, and Government Challenges, 2018)
The objectivites of the research is to find out empirical evidence of the determine audit quality in mediating the relantionship between KAP size, KAP tenure and earnings managemen. The population of this study was listed companies in the manufacturing sector at the Indonesia Stock Exchange, and the sample was determined based on following criteria: (a) the annual report ended 31 December, (b) not include in financial secto, ect. There were 355 companies meeting the criteria. The technique used is the analysis of Partial Least Square (PLS). Theresult of this research show that (1) KAP size have significant effect on audit quality; (2) KAP tenure have significant effect on audit quality; (3) Audit quality have significant effect on earning management; (4) KAP size capable of being mediating variabel in the relantionship between KAP size with earning management; (5) KAP Tenure does not capable of being mediating variable in the relantionship between KAP tenure with earning management